Avañe'e, ñe'e tavy, karai ñe'e: escolarização do guarani e diglossia no Paraguai - Sebastião Peres (Associação Sul-Rio-Grandense de Pesquisadores em História da Educação (ASPHE), 2012)
O Paraguai apresenta uma situação de profunda desigualdade social: 10% da população detém 42% da riqueza; 40% da população detém 10% da riqueza. Vinculada a isto, apresenta uma situação de diglossia: 39,2% dos paraguaios são monolingües em guarani e 6,4% monolingües em castelhano. Porém, a escola sempre utilizou como língua de ensino o castelhano, gerando elevados índices de insucesso escolar. Com a oficialização do guarani em 1992, intensificou-se a discussão sobre qual modalidade utilizar na escola: o jopara, guarani interferido pelo castelhano, utilizado cotidianamente, ou o guaraniete, guarani puro, acadêmico. A identificação do guarani como língua da pobreza provoca rejeições quanto à sua escolarização. No passado, o castelhano era considerado a língua dos senhores, e o guarani a língua do povo. A escolarização do guarani pode resultar na sua senhorização. Palavras-chave: língua guarani, Paraguai.   Abstract Paraguay presents a situation of deep social inequality: 10% of its population owns 42% of the country richness, while 40% of its population owns no more than 10% of the country richness. Linked to this, it presents a situation of diglossia: 39,2% of Paraguayans speak only guaranian and 6,4% speak only Castilian. In spite of this situation, the school system has always used Castilian as the teaching language, which caused high rates of school failure. After the officialization of the guaranian language in 1992, the discussion on which modality should be used in the school increased: the jopara, a guaranian intervened by Castilian, which is used daily, or guaraniete, a pure academic guaranian. Guaranian identification as poor people language gives rise to rejections as to its use in school. In the past, Castilian was considered the masters' language, while guaranian was seen as the language of underlings. The schooling of guaranian, that is, its introduction into school, may mean its masterization, that is, its ascent to the level of a master's language. Keywords: guaranian language, Paraguay.